Screening of Enteric Fever in the Human Population of District Khairpur, Sindh, Pakistan - Javed Ahmed Ujan, Zeeshan Khokhar, Shazia Solangi, Paras Soomro, Kaneez Ul Hussain, Shaista Ghumro, Kainat Mahar, Mir Muhammad Ali Talpur, G. Ali Mallah, Shahnawz Ujan (Pakistan Journal of Medical & Health Sciences, 2022)
Typhoid fever, commonly known as enteric fever, is a bacterial infection that can affect many organs and spread throughout the body. Bacteria known as Salmonella typhi are the most common cause of Typhoid/ Enteric fever; the same bacteria are also most commonly involved in food poisoning. Typhoid fever is more common in areas with contaminated water and food and poor sanitation. In crowded and unsanitary places, typhoid fever is one of the most common causes of death and morbidity. Headaches and stomach pain are frequently associated with this fever. A course of antibiotics, vaccine prophylaxis, various care, surgery, and sanitation prevention are usually effective treatments for typhoid fever. Antibiotics are exclusively effective against typhoid fever, and the most prescribed antibiotics are Ciprofloxacin and Ceftriaxone. The primary goal of the present study was to diagnose typhoid fever using a Widal test, estimate the percentage prevalence of typhoid-affected patients according to their age and gender, and compare the percentage of typhoid-affected patients in different parts of Khairpur Mir’s district. During data collection, 143 tests of typhoid fever were performed with the human population of different areas of District Khairpur Mirs. Results of this study showed a total of 83 (58.04%) of positive cases in males, and 60 (41.95%) were positive in females; among them, 73 (51.04%) patients were above the age of 25, and 70 (48.95%) were below the age of 25, 70 (48.04%) patients were diagnosed with typhoid fever while others were not affected. According to the area, Lukman contains 27 (18.88%) of the positive cases; mall road contains 28 (19.58%) cases, Punjhuti contains 29(20.27%) cases, Bhens colony contain 30 (20.97%) cases and Milk colony 29 (20.27%) patient of typhoid fever. Present work will be helpful for the spread of awareness of typhoid fever at District Khairpur Mirs.